Edukasi Pertolongan Pertama Kasus Gawat Darurat Gigi pada Remaja Wilayah Kayu Mas Jakarta Timur - Faudah Amin, Meiny; Yusra, Yohana; Juliawati, Mita; Kusnoto, Joko; Ie Elline (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2023)
Emergency dental issues such as throbbing toothaches, dental trauma (fractures, dislodgment from the gums), teeth pierced by orthodontic wires, and wires from dental braces causing injuries by piercing the gums, are some of the health problems that can result in prolonged suffering for those experiencing them. Every case has a different level of emergency. Although for some people it is not considered a real emergency, it is still a condition that urgently requires proper action before going to the dentist. Therefore, there is a need for increased knowledge to provide first aid before visiting a dentist. Collaborative efforts between medical professionals, alumni, and professional students from the Faculty of Dentistry at Trisakti University conducted an activity involving education for the adolescent community at the Integrated Child-Friendly Public Space (RPTRA) in Kayu Mas, East Jakarta, on March 16, 2023. Before and after the distribution of education, pre and post-tests were conducted, showing significant improvements in knowledge regarding dental emergencies. The conclusion drawn from this activity underscores the importance of knowing the initial steps to handle dental emergencies in order to receive appropriate medical care.